Christianity, Wealth, and Spiritual Power in Ghana - Lauterbach, Karen (Springer International Publishing, 2017)
This book centers around mid-level charismatic pastors in Ghana. Karen Lauterbach analyzes pastorship as a pathway to becoming small “big men” and achieving status, wealth, and power in the country. The volume investigates both the social processes of becoming a pastor and the spiritual dimensions of how power and wealth are conceptualized, achieved, and legitimized in the particular context of Asante in Ghana. Lauterbach integrates her analysis of charismatic Christianity with a historically informed examination of social mobility-how people in subordinate positions seek to join up with power. She explores how the ideas and experiences surrounding the achievement of wealth and performance of power are shaped and re-shaped. In this way, the book historicizes current expressions of charismatic Christianity in Ghana while also bringing the role of religion and belief to bear on our understanding of wealth and power as they function more broadly in African societies